2020
DOI: 10.2351/7.0000074
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the melt ejection and burr formation during laser fusion cutting of stainless steel

Abstract: When the melt is ejected from the cut kerf by an assist gas during laser fusion cutting, a fraction of it may adhere to the lower cut edge and form a burr. Adjusting the process parameters to minimize burr formation is a challenging task that becomes more and more difficult as sheet thickness increases. The burr length has significant relevance when the quality of a cut is evaluated, but the underlying mechanisms that control its formation are still not fully understood. In this paper, new results of an experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…Therefore, a high number of cross-sections per cut have to be performed to gain reliable results. Observing the melt flow is common to draw conclusions about the cutting result [21,22,[26][27][28][29][30][31]. Due to the limited accessibility of the process zone, artificial conditions have been created for process observation [21,27,28] or complex experimental setups have been designed [21,22,[27][28][29][30], which are not suitable as standard evaluation.…”
Section: Measurement Methods To Determine the Limiting Mechanisms Of ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, a high number of cross-sections per cut have to be performed to gain reliable results. Observing the melt flow is common to draw conclusions about the cutting result [21,22,[26][27][28][29][30][31]. Due to the limited accessibility of the process zone, artificial conditions have been created for process observation [21,27,28] or complex experimental setups have been designed [21,22,[27][28][29][30], which are not suitable as standard evaluation.…”
Section: Measurement Methods To Determine the Limiting Mechanisms Of ...mentioning
confidence: 99%
“…Observing the melt flow is common to draw conclusions about the cutting result [21,22,[26][27][28][29][30][31]. Due to the limited accessibility of the process zone, artificial conditions have been created for process observation [21,27,28] or complex experimental setups have been designed [21,22,[27][28][29][30], which are not suitable as standard evaluation. Nevertheless, the investigations found that melt flow generates striations [21,27] and influences burr attachment [29].…”
Section: Measurement Methods To Determine the Limiting Mechanisms Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Adjusting the process parameters to minimize burr formation is a challenging task that becomes more and more difficult as sheet thickness increases. Stoyanov et al [75] studied the dynamics of the melt during its ejection from the kerf. A melt ejection forming a compact and stable threefold outflow is a characteristic property of a burr-free cut.…”
Section: Fusion Cuttingmentioning
confidence: 99%
“…Se realiza la siguiente revisión bibliográfica, en donde se destacarán algunos autores acompañados de sus ideas. Dentro de los artículos revisados y relacionados al proceso productivo de corte convencional o láminas de acero, se pudo evidenciar que dentro de los procesos de simulación se implementan distintas técnicas de modelamiento que incluyen herramientas de programación que ayudaran a los gerentes a tomar decisiones que les permitan ser competitivos [7,8,9,10]. Con el modelado dinámico, según [11], se pueden probar cambios antes de realizarlos, como, por ejemplo, justificar la contratación de un mayor número de personal obrero, comprar máquinas, entre otros.…”
Section: Revisión Bibliográficaunclassified